1993
DOI: 10.1161/01.cir.88.2.416
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of 6-month mortality in survivors of myocardial infarction after thrombolysis. Results of the GISSI-2 data base. The Ad hoc Working Group of the Gruppo Italiano per lo Studio della Sopravvivenza nell'Infarto Miocardico (GISSI)-2 Data Base.

Abstract: A decline in 6-month mortality of myocardial infarction survivors, seen within 6 hours of symptom onset, has been observed in recent years. Ineligibility for exercise test, early left ventricular failure, and recovery-phase left ventricular dysfunction are the most powerful (RR, > 2) predictors of 6-month mortality among patients recovering from myocardial infarction after thrombolysis. Qualitative variables reflecting residual myocardial ischemia do not appear to be risk predictors. The lack of an independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
2
7

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(109 citation statements)
references
References 104 publications
(20 reference statements)
0
100
2
7
Order By: Relevance
“…This process is called "LV remodeling" (Jessup and Brozena 2003). The development of LV remodeling leads to heart failure, sudden cardiac death, and poor prognosis (Volpi et al 1993). It is reported that capillary density in the border zone is negatively correlated with infarct size one month after AMI, suggesting the importance of the adequate growth of the capillary microvasculature (Olivetti et al 1986).…”
Section: Extracorporeal Sw Therapy For Acute Myocardial Infarction Anmentioning
confidence: 99%
“…This process is called "LV remodeling" (Jessup and Brozena 2003). The development of LV remodeling leads to heart failure, sudden cardiac death, and poor prognosis (Volpi et al 1993). It is reported that capillary density in the border zone is negatively correlated with infarct size one month after AMI, suggesting the importance of the adequate growth of the capillary microvasculature (Olivetti et al 1986).…”
Section: Extracorporeal Sw Therapy For Acute Myocardial Infarction Anmentioning
confidence: 99%
“…Um dos principais fatores prognósticos de mortalidade cardíaca após infarto é a função ventricular esquerda 118 , com maiores incrementos da mortalidade associados à redução progressiva da fração de ejeção ventricular, considerando-se pacientes de alto risco aqueles com fração de ejeção ventricular esquerda menor que 35% 119 .…”
Section: -Ecocardiografia Dopplerunclassified
“…Details pertaining to acquisition and analysis of echocardiographic data have been reported elsewhere. 16 Measurement of BNP and indices of collagen metabolism Blood samples were taken at least 30 min before sampling, with the patient resting in semi-recumbent supine position. For BNP, blood samples were collected into ethylene diamine tetra acetic acid and aprotinin (500 KIU ml À1 ) plastic tubes; plasma was separated by centrifugation 2000 g at 4 1C and stored at À80 1C until analysis.…”
Section: Echocardiographymentioning
confidence: 99%
“…6 LV systolic dysfunction was defined as an echocardiographic LVEF p40%. 16 A restrictive LV filling pattern was defined as a Doppler mitral E wave deceleration time (DT) p130 ms. 17 Coronary restenosis was defined as a X50% diameter stenosis of the infarct-related artery at follow-up angiogram.…”
Section: Definitions and Outcome Measuresmentioning
confidence: 99%